MEANINGFUL ASSESSMENT FOR WRITING AT ISLAMIC UNIVERSITIES - Dedi Irwansyah (Jurnal Pedagogy, 2016)
The term ‘meaningful’ or ‘authectic’ assessments might be understood variously depending on the charateristics of the learners and the type of educational setting. General universities and Islamic universities are likely to employ the terms differently. It is no secret that an Islamic university seeks to integrate Islamic values into all aspects of its English Language Teaching (ELT) curriculum including writing assessment. The fact that Muslims constitue a vast number of English learner in Indonesia has not yet been adequately supported by assessment procedures designed to guide the English instruction. The assessments in every teaching level is suppossed to be meaningful. To design a meaningful assessment tasks for a writing course in Islamic universities, teachers should consider the growing number of Islamic terms and Islam-related expressions in the field of English language education. The terms and expressions could be integrated into imitative, intensive, responsive, and extensive writings. This paper focuses on meaningful assessment for writing course in Islamic university, an area on which researchers have not conducted adequate analyses.